2019
DOI: 10.3390/coatings9030188
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of YSZ Suspensions and Coatings

Abstract: The demand for suspensions that are used in thermal spray processes is expanding from research labs using the lab-prepared suspensions toward actual coating production in different industrial sectors. Industrial applications dictate the reduced production time and effort, which may in turn justify the development of the market for ready-to-use commercial suspensions. To this end, some of the powder suppliers have already taken steps forward by introducing, to the market, suspensions of some of the most used ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Relatively small Stokes number (St\ 1) indicates increased probability of droplets approaching the substrate at more oblique angels (Ref 18, 39). Formation of columnar coatings from water based precursor solutions could be related to the small droplet sizes increasing the chance of having small Stokes numbers ( Ref 40,41). This is in accordance with the droplet size distribution measurements of atomized solutions as discussed above (17.4 and 15.9 lm for 0.5 and 0.125 M concentrations of water based solutions, respectively).…”
Section: Coatings Characteristicssupporting
confidence: 79%
“…Relatively small Stokes number (St\ 1) indicates increased probability of droplets approaching the substrate at more oblique angels (Ref 18, 39). Formation of columnar coatings from water based precursor solutions could be related to the small droplet sizes increasing the chance of having small Stokes numbers ( Ref 40,41). This is in accordance with the droplet size distribution measurements of atomized solutions as discussed above (17.4 and 15.9 lm for 0.5 and 0.125 M concentrations of water based solutions, respectively).…”
Section: Coatings Characteristicssupporting
confidence: 79%
“…The injection of the suspension has also been an object of study [17]. Some of those conclusions showed that coating microstructure and performance are related to the suspension characteristics [18]. Ganvir et al [19] studied the evolution of the coating microstructure during spray.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudo-columnar growth of the nano-structured suspension PS YSZ coatings has turned out to be sensitive to a number of deposition parameters like the average particle size, liquid carrier composition, flow rate, the ratio of solid to liquid, and stand-off distance [13,16,[20][21][22]. The formation of this characteristic microstructure is sought in the operation of strong drag force exerted on in-flight solidified drops by a working gas, which is surpassing the adhesion force on the impact on a flat surface [23,24].…”
Section: Discussionmentioning
confidence: 99%